PENERAPAN PERGERAKAN KAMERA DINAMIS PADA FILM “SAMSARA” UNTUK MENCIPTAKAN KESAN MENEGANGKAN - Helvin Topannesa; I Kadek Puriartha; I Made Denny Chrisna Putra (CALACCITRA: JURNAL FILM DAN TELEVISI, 2021)
Samsara film is an action drama genre film with the story preaching an emotional and tense feeling as an experience for each audience, the writer is responsible for determining the cinematographic concept that will be used in samsara films in supporting the needs of narrative elements in the film. Based on this the authors as cinematographers chose to apply dynamic camera movement techniques, to provide elements of dramatic, realism and audience participation. In embodying the concept the writer uses qualitative description methods such as observation of the reference film, interviews with Ical Tanjung as a national cinematographer, opinion surveys about dynamic camera movements to the public and supported by cinematographic theories from Joseph V.Mascelli and Himawan Pratista who explain Framming : composition, angle, continuity, lighting, color and aspect ratio and camera movement. In realizing cinematographic techniques in Samsara films, in addition to using cinematographic elements such as angles, three point lighting, aspect ratio and type of shot, the writer also uses handheld techniques because basically dynamic cameras have a flexible nature and move freely to follow the movement of the story so that each battle scene, Dramatic and tense moments in his preformance can be easily enshrined to build mood and support the narrative element needs of Samsara films.